Ефективностa на корпоративното управување во Република Македонија - Блажевска, Анита (Економски факултет, УКИМ, Скопје, 2016)
The effectiveness of the corporate governance is one of the most important aspects thereof. The corporate governance gains special significance particularly after the occurrence of a large number of corporate scandals. The effectiveness largely depends on the issues such as the organisation of the boards, their composition, the establishment of commissions, the efficiency of the meetings of the board of directors, the role of the president of the board and the separation of the role of the president of the board from the role of the chief executive officer. The efficient functioning of the board of directors implies structuring of the board in accordance with the regulatory requirements, but also at the same time it implies existence of culture and challenges in the board of directors, continuous evaluation of the board of directors, and especially evaluation of the chief executive officer which is a key issue in the evaluation system. The modern corporate governance also deals with conflict of interest between different groups of stakeholders, such as the owners, the employees, the managers, etc. As a result of the internationalisation of the cross-border portfolios and the financial crisis that affected many parts of the world, perhaps it is not surprising that many institutional investors are more carefully scrutinizing the corporate governance of the companies. In order to get a complete perception about the effectiveness of the corporate governance in the Republic of Macedonia, an empirical survey was conducted in 50 large joint stock companies.
Докторска дисертација одбранета во 2016 година на Економскиот факултет во Скопје, под менторство на проф. д–р Бобек Шуклев.
Keywords: corporate governance, effectiveness of corporate governance, efficiency of board of directors, president of the board of director, chief executive officer, evaluation, responsibility, competency, institutional investors